The impact of tax revenue on Azerbaijan’s economic growth - Akbulaev, Nurkhodzsa (Public Finance Quarterly, 2024)
Tax revenues that the state obtains by force from its citizens based on its sovereign authority make up the majority of public revenues and influence financial policy. Economic development is the first financial policy aim. Tax revenues impact economic growth directly and indirectly through savings, consumption, output, and employment. Many macroeconomic factors improve with economic expansion. Economic growth boosts economic activity and tax income. This research examines Azerbaijan’s tax kinds, tax revenues, and economic development from 1991 through 2021. Tax revenues and economic growth were analysed using time series methods. Unit root and Maki structural break cointegration tests were employed. In the research with three structural breakdowns, a long-term cointegration connection was discovered between tax revenues and economic growth in all models.